PENGEMBANGAN BUKU PINTAR BERBASIS INFORMATION AND COMMUNICATION TECHNOLOGY PADA PEMBELAJARAN TEMATIK DI KELAS V SD NEGERI 02 CISAMPIH LEBAK – BANTEN - Neng Nurlela (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Thematic learning links one lesson to another. SD Negeri 02 Cisampih is still less than optimal in preparing technology-based learning activities, especially nowadays, it is still in a situation of the covid-19 pandemic, which limited the students to study directly at school. SmartBooks are an alternative to provide the understanding and foster enthusiasm and motivation for students in thematic learning. This study aimed to determine the feasibility of the SmartBook, find out the exact validity of the SmartBook media, and find out the response to the book. This research was conducted at SD Negeri 02 Cisampih. The research subjects were 19 students at grade V in a limited trial. The type of research referred to the research and development (R&D) model. This model consisted of 10 stages namely, (1) potential and problems, (2) information gathering, (3) product design, (4) design validation, (5) design revision, (6) product trial, (7) product revision, (8) usage trial, (9) final product revision, (10) mass production. This research only reached stage 6, namely product testing. The instrument was a questionnaire sheet for media validation with a percentage of 86.5%, material validation with a percentage of 89.5%, education experts with a percentage of 86.5%, and a student response questionnaire sheet of 84%. Based on the data analysis, it was concluded that the quality of the SmartBook was in the very decent category. Meanwhile, the results of students’ responses to SmartBooks were in the very good category.